Pendekatan Algoritma Naïve Bayes dan Support Vector Machine dalam Menganalisis Tanggapan Terhadap Penutupan Tik Tok Shop - kurniawan, Fandi; Al Qorni, Qois (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2023)
The development of information technology, especially in social media such as TikTok, has had a significant impact on people's shopping behavior patterns. Sentiment analysis is aimed at understanding general views regarding the closure of the TikTok Shop, describing positive or negative opinions. The algorithms used are Naïve Bayes and Support Vector Machine (SVM) to analyze responses to the closure of the TikTok Shop. The research methodology involves the process of crawling the Twitter dataset with the keyword